2013
DOI: 10.1159/000346836
|View full text |Cite
|
Sign up to set email alerts
|

Clinically Meaningful Responses to Sequential Gemcitabine-Based Chemotherapy Regimens in a Patient with Metastatic Pancreatic Cancer

Abstract: Pancreatic cancer exhibits profound chemoresistance resulting either from pre-existing (intrinsic) mechanisms, or from anticancer drug treatment itself (acquired chemoresistance). We present the case of a patient with pancreatic adenocarcinoma metastatic to the liver who experienced clinical, radiographic and tumor marker response to three lines of gemcitabine-based chemotherapy. The regimens included: 8 cycles of gemcitabine and oxaliplatin (GEMOX), 8 cycles of gemcitabine, docetaxel and capecitabine (GTX) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…However, the metabolic response of hepatic lesions was heterogeneous with some lesions showing no response to therapy, even in patients where other lesions responded with complete loss of metabolic activity. This disparity in response observed between primary and metastatic lesions can be observed by FDG-PET imaging in some patients receiving standard chemotherapy alone (28-30). Here, we have used FDG-PET/CT imaging to demonstrate and quantify heterogeneity in metabolic responses observed with therapy in PDA.…”
Section: Discussionmentioning
confidence: 99%
“…However, the metabolic response of hepatic lesions was heterogeneous with some lesions showing no response to therapy, even in patients where other lesions responded with complete loss of metabolic activity. This disparity in response observed between primary and metastatic lesions can be observed by FDG-PET imaging in some patients receiving standard chemotherapy alone (28-30). Here, we have used FDG-PET/CT imaging to demonstrate and quantify heterogeneity in metabolic responses observed with therapy in PDA.…”
Section: Discussionmentioning
confidence: 99%
“…Chue et al [249] reported of a patient with metastatic PDAC who responded extremely well to (five years from diagnosis until report published) treatment with metronomic dosing of POLF (pa clitaxel+oxaliplatin+leucovorin+5-FU) and a gemcitabine-based regimen, including oxaliplatin and leucovorin/5-FU with intemittent cetuximab (EGFR inhibitor). It is noted that the patient's tumour showed no KRAS mutation indicating that wild-type KRAS responds to cetuximad and contributes to patient's unusual long survival [248] Klimant et al [250] presented a case of a patient with PDAC metastatic to the liver who experienced gemcitabine-based chemotherapy. The regimens included cycles of gemcitabine and oxaliplatin (GEMOX), followed by cycles gemcitabine, docetaxel and capecitabine and then cycles of gemcitabine and nab-paclitaxel, with an exceptional response 2 years from the initiation of chemotherapy for metastatic pancreatic cancer [250].…”
Section: Exceptional Respondersmentioning
confidence: 99%
“…It is noted that the patient's tumour showed no KRAS mutation indicating that wild-type KRAS responds to cetuximad and contributes to patient's unusual long survival [248] Klimant et al [250] presented a case of a patient with PDAC metastatic to the liver who experienced gemcitabine-based chemotherapy. The regimens included cycles of gemcitabine and oxaliplatin (GEMOX), followed by cycles gemcitabine, docetaxel and capecitabine and then cycles of gemcitabine and nab-paclitaxel, with an exceptional response 2 years from the initiation of chemotherapy for metastatic pancreatic cancer [250]. Although genetic testing were not performed in this patient, patient's exceptional response to these treatments may lead to the conclusion that this patients' tumour may have had a unique genetic and molecular makeup.…”
Section: Exceptional Respondersmentioning
confidence: 99%
“…The origin of this study derives from the observation of fınding the occasional "exceptional response" (objective response; i.e., durable) in otherwise negative phase II clinical trials of new agents, or with agents used in the clinic. 4,5 It is not uncommon to fınd in such studies, or sometimes in clinical practice, a few patients whose tumors seem to respond to an agent that does not exhibit any sign of benefıt in the majority of patients treated for a specifıc cancer diagnosis. This study ( Fig.…”
Section: Exceptional Responders Initiativementioning
confidence: 99%